Clinicodemographic Profiling of Zika Outbreak in Jaipur, Rajasthan - Raman Sharma; Madhulata Agarwal; Mayank Gupta; Ruchi Singh; Sunil Kumar Mahavar; Rajni Sharma; Deepa Meena (Indian Journal of Medical Specialities)
Background: The 2018 postmonsoon outbreak of Zika virus infection, in a localized pocket of city of Jaipur, Rajasthan, so far the largest in India, alarmed the health authorities to optimize surveillance and measures. Hence, a community-based study to analyze the clinicodemographic profile was conducted to gain better understanding of its squeal. This study aimed to analyze the clinicodemographic profile of this new entrant viral infection. Methods: The study was designed as a community-based observational study. 1,488,870 people in vicinity of the index case were surveyed clinically from October to November 2018. A total of 1925 febrile individuals including pregnant ones in various trimesters of their pregnancy were screened for Zika infection by reverse-transcriptase-polymerase-chain-reaction (RT-PCR). Among these, 153 were RT-PCR positive and 111 cases consenting for the study were included and data collected were analyzed using SPSS 16 software. Results: The mean age of the study population was 27.51 years (95% confidence interval = 24.78–30.25), 53% of the patients were females. Out of 59 Zika-positive females, 27 (46%) were pregnant; 12 (44.4%) were in first trimester and 9 (33%) and 6 (22.2%) in second and third trimester, respectively. The incubation period ranged from 2 to 10 days, the most common symptom being low grade fever in 82%, followed by myalgia in 64.9% and arthralgia in rheumatoid distribution in 55.9%. On examination, a widely distributed blanching maculopapular rash was seen in 28.8%; nonpurulent conjunctivitis differentiating it from dengue was seen in 16.2%. Conclusions: Although Zika, a commonly prevalent virus in dengue endemic belts, yet unknown to our territory, usually causes a mild febrile illness, it can be a cause of intense apprehension to many if infection occurs in the first trimester of pregnancy. Formulating guidelines to tackle Zika pregnancy is a daunting task and needs collaboration across the globe to carry out future research and to get the knowhow.